[OP.3D.03] ASSOCIATION BETWEEN NEUTROPHIL TO LYMPHOCYTE RATIO AND ARTERIAL STIFFNESS IN A POPULATION SAMPLE. (September 2016) - Huguet, E.; Maccallini, G.; Pardini, P.; Obregon, S.; Hidalgo, M.; Haehnel, M.; Carrizo, P.; Koretzky, M.; Di Leva, A.; Inserra, F.; Botto, F.; Scuteri, A.; et al.
Abstract : Objective: Immuno-inflammation plays a key role in the process of atherosclerosis and vascular stiffness as surrogates for Early Vascular Ageing (EVA). Our aim was to evaluate the association between the Neutrophil to Lymphocyte Ratio (NLR), a validated inflammatory marker, and arterial stiffness represented by the pulse wave velocity (PWV), in a population-based sample. Design and method: We included prospectively 237 adults who attended for cardiovascular screening tests. They provided data about lifestyle and cardiovascular history by completing the WHO STEPS Survey. NLR was calculated by dividing the number of neutrophils by number of lymphocytes from peripheral blood sample. PWV was determined by the Mobil-O-Graph device. Using regression models we explored the association between NLR and PWV, adjusted for baseline variables. Results: Mean age of population was 52.7 ± 23.8 years, 45% female. Risk factors prevalence was: diabetes 8.4%, active smoking 33%, hypertension 43%, and dyslipidemia 29%.Unvariable analyses showed that NLR (p < 0.001), age (p < 0.0001), hypertension (p < 0.0001) and smoking (p = 0.04) were significantly associated to PWV. By multivariable regression analysis, NLR demonstrated a linear and independent relationship with PWV, adjusted for smoking, diabetes, dyslipidemia and hypertension. Conclusions: The Neutrophil to Lymphocyte Ratio (NLR) was independently associated to arterial stiffness determined by PWV, which may suggest a state of chronic inflammation contributing to arteriosclerosis development. NLR could represent an inexpensive resource to predict vascular stiffness, EVA and high cardiovascular risk.